The influence of teachers’ and learners’ attitudes on mathematics performance in selected rural secondary schools in Vhembe West District - Mafhenya, Michael (University of the Free State, 2020)
The study investigated the influence of teachers’ and learners’ attitudes in Mathematics performance. The researcher used a mixed methods research approach in this study, which means that both qualitative and quantitative research approaches were used. The study’s design was a sequential explanatory mixed method design. The following instruments were used to collect data for this study; a closed-ended questionnaire for teachers, a semi-structured interview schedule for teachers as well as a closed-ended questionnaire for learners. The questionnaires were tested for reliability using the Cronbach coefficient while a pilot study was conducted for validity. Convenience sampling was used to select the five schools that participated. The one hundred and thirty (130) learners and thirty (30) educators who participated in the quantitative stage were randomly sampled, while the fifteen (15) educators for the qualitative stage were conveniently sampled. The Statistical Package for Social Sciences (SPSS) Version 25 was used to analyse the responses from the quantitative data, and was presented in frequencies and percentages generated to explain all variables under study. Qualitative data analysis was through content analysis. For the qualitative analysis, the researcher studied the data to become familiar with it in order to identify the themes. Using this analysis method enabled the researcher to identify key words and ideas raised repeatedly by participants. The findings helped to unfold the influence of teachers and learners attitudes in Mathematics performance. The study found that learners’ attitudes are triggered by various factors that range from teacher-centred to learner-centred, and teacher’s understanding of learners thinking in Mathematics has an effect on developing learner attitude. It also emerged that nearly three quarters of teachers were learning how to use inquiry-oriented teaching strategies and around 90% were learning how to assess learners in Mathematics. In addition, lack of material for learning Mathematics generates a negative attitude, while poor learner performance in Mathematics leads to dislike for the subjects. The study concluded that teaching style and learners’ motivation to learn affected attitude towards Mathematics. Though educators taught the subject very well, some learners did not have interest. The study also concluded that while teachers indicated that they received support from other Mathematics teachers and the management of the schools, and that the Department of Basic Education was putting effort through Mathematics workshop for teachers, the majority of teachers indicated that they were either not getting support from the parents of the learners or the support was minimal. Furthermore, most teachers responded that they did not have a good foundation in Mathematics, and that there were different ways through which learners’ attitudes influenced their performance in Mathematics including interest or aversion due to lack of understanding. Most learners believed that Mathematics was difficult, and it took a long time to understand the concepts. The study recommends that the Department of Education (DoE) must support Mathematics by building enough classrooms and hiring more Mathematics teachers. This will make the classrooms conducive for learning. In addition, the DoE should ensure that a manageable number of learners are in one classroom to minimise overcrowding. Overcrowding makes it difficult for teachers to be effective as they may not be able to mark work for every learner or monitor each learner’s performance. The study recommends that the DoE should also provide enough learning materials and consider utilisation of electronic materials to save paper, money and the environment. Ultimately, parents should support the teachers by being involved in their children’s education, they should buy their children Mathematics materials, assist them with homework and arrange extra classes for them. If teachers and parents work together to assist these learners, the learners’ performance can improve.
Keywords: Dissertation (M.Ed. (School of Education Studies))--University of the Free State, 2020; Mathematics; Teachers; Learners; Attitudes and performance